Design and analysis of solar assisted mini desalination plant using waste humid air of energy tower suitable for small community. Issue 4 (21st December 2022) - Sachdev, Taranjeet; Gaba, Vivek Kumar; Tiwari, Anil Kr
ABSTRACT: The aim of this work is to design and analyze solar humidification and dehumidification desalination plant that is integrated with an energy tower. The proposed integrated water production plant (IWPP) utilizes the waste humid air of the energy tower for the production of potable water as an added benefit in bonus apart from the power production through energy tower. The layout of the proposed desalination plant has been presented which is configured with 100 solar humidification dehumidification desalination units and capable to fulfill potable water demand of 800 liters per day that may be sufficient for a small community of remote area. The seasonal and annual performance of the plant has been analyzed in the climatic condition of Jamnagar which is hot and humid city in western Indian state, Gujarat. The optimum values of air and water mass flow rate have been identified with the help of mathematical simulations in summer, rainy and winter season. The results showed that air mass flow rate 118–120 kg/hr through solar air heater is suitable for water production throughout the year. The water mass flow rate of 125–130 kg/hr in humidifier and 120 kg/hr−122 kg/hr in dehumidifier has been found optimum for potable water production. The seasonal variation in gain output ratio is 0.32−0.45 however it can be increased to 0.62 at optimized operating condition. Finally, the economic and environmental analysis of the proposed plant resulted Rs 0.93/kg (US $ 0.011/kg) cost of potable water, payback period of 0.49 year and 146.8 t/annum reduction in CO2 emission, respectively. HIGHLIGHTS: Mini desalination plant capable to fulfill water needs of small community. Utilization of waste humid air of energy tower Clean source of potable water. Numerical analysis for time dependent behavior. Annual performance, economic and environment analysis.